Preparation and Performance Test of PEFB Reinforced Box Waste Coated Superhydrophobic Coating for Shoe Sole Application - Marsi, Noraini (International Journal of Integrated Engineering, 2020)
The study presents preparation and performance test of Palm Empty Fruit Bunches (PEFB) reinforced box waste coated superhydrophobic coating for shoe sole application. The main purpose of this analysis is to determine the optimal composition of PEFB reinforced with box waste for use in shoe soles. In this study, the use of PEFB and box waste is to replace the synthetic materials in the application of the shoe sole. Additionally, the environmental problems can be reduced by using waste PEFB as a value-added product rather than biomass waste. Sample preparation involved grinding of PEFB fibers and box waste, blending processes of different PEFB percentages at 20%, 40%, 60% and 80% mixed with 50% box waste. Followed by the process of mixing with epoxy and hardener, and finally coated with superhydrophobic coating using spray gun method. Epoxy resin and hardener are used as binder for the bonding between the PEFB fiber matrix and the box waste to be applied to the shoe sole. The study was carried out in both mechanical and physical studies. The test for tensile strength showed 40% PEFB reinforced with 50% box waste with 181.36N maximum load and 16.70% of strain. The 40% PEFB composition showed the optimum bursting pressure to 13.62kgf and the abrasion resistance had the lower weight loss of 0.28 g. The 80% higher proportion of PEFB indicates a lower density of 1.06g/cm3 and a higher porosity of up to 0.44%. It is also revealed that 40% box waste provided the best composition for the application of the shoe soles.